Lespedeza hengduanshanensis comb. & stat. nov. (Leguminosae: Papilionoideae: Desmodieae) from the Hengduan Mountains of SW China - Xu, Bo; Gao, Xin-Fen; Zhang, Libing (Phytotaxa, 2015)
Lespedeza fasciculiflora Franchet is currently divided into two varieties, var. fasciculiflora and var. hengduanshanensis C.J. Chen. A detailed comparison of the plants from wild populations and specimens of the two varieties revealed that var. hengduanshanensis was sufficiently distinct from var. fasciculiflora to be recognized as a separate species. Our phylogenetic analysis based on DNA sequences, moreover, showed that the two varieties are not even closely related. We therefore here elevate the status of L. fasciculiflora var. hengduanshanensis to species L. hengduanshanensis (C.J. Chen) B. Xu, X.F. Gao & Li Bing Zhang, comb. & stat. nov..